De la scolarité souffrante (compléments à "De l'école au Mali") (Nordic Journal of African Studies, 2000)
This is a follow-up of a first article published in this same review in 1997. It develops further some of its major themes, for instance the necessity of better quality in the Malian system of education, the need of lucidity on the part of the educational authorities, the problem of national languages, and the concept of a ‘classroom school’ (classe-école, i.e. a school reduced to one class). The idea that just a small minority of children are actually affected by school problems is also developed.